A nation in the red The government debt crisis and what we can do about it - Holland, Murray (New York McGraw-Hill Education, 2014)
Our government debt is rising every day. Our population is shifting as more people retire and fewer are able to find work. Our social programs, including the Affordable Care Act, are only adding to our financial burden, and rising taxes are hindering economic growth. We are a nation in the red.

A powerful wake-up call to leaders, investors, and citizens, this brilliantly researched book reveals the surprising truth about our national debt--and what we can do about it.
A nation in the red -- Real numbers -- The debt trap -- The financial causes of the debt trap -- Psychological causes of the debt trap -- The European economic and currency crises -- The 5 ways out of the debt trap -- Can the United States escape the debt trap? -- What does all this mean to you and how can you help?
Includes bibliographical references (pages 259-266) and index
Keywords: Debts, Public -- United States; Government spending policy -- United States; Financial crises -- United States; United States -- Economic conditions -- 2009-.; United States -- Economic policy -- 2009-.